1978
DOI: 10.1159/000144972
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural morphometric study on developing acinar cells of the rat pancreas and parotid gland

Abstract: The fraction of cellular volume occupied by the cytoplasm has been assessed by point-counting volumetry in 0.5-μm araldite sections. Measurement of the transection radius of the nuclei of acinar cells allowed the assessment of the mean nuclear volume according to the method of Bach. With these data, the cytoplasm volume was calculated in cubic micrometers. Ultrastructural morphometric data were obtained by means of superimposing on the electron photomicrographies (× 21,000 or × 28,500) a test system of 84 even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1979
1979
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…During this period the relative rise in cell size and thereby in the quantity of cytoplasmic organelles is the highest of all ontogenetic development. FERRAZ DE CARVALHO et al (1978) showed morphometrically that between days 10-40 the total surface of the rough endoplasmic BIGNARDI (1961) studying histochemically the early postnatal evolution of the rat parotid gland observed in 5-day-old rats another cell type containing clear secretory granules exhibiting PAS and Alcian blue positive materials. These observations were confirmed by LAWSON (1970) in rats of 3-4 days of age.…”
Section: Myoepithelial Cellsmentioning
confidence: 99%
“…During this period the relative rise in cell size and thereby in the quantity of cytoplasmic organelles is the highest of all ontogenetic development. FERRAZ DE CARVALHO et al (1978) showed morphometrically that between days 10-40 the total surface of the rough endoplasmic BIGNARDI (1961) studying histochemically the early postnatal evolution of the rat parotid gland observed in 5-day-old rats another cell type containing clear secretory granules exhibiting PAS and Alcian blue positive materials. These observations were confirmed by LAWSON (1970) in rats of 3-4 days of age.…”
Section: Myoepithelial Cellsmentioning
confidence: 99%
“…Although no strong evidence has been available to indicate the direct relationship of this ATPase activity to plasma membrane Ca2+-flux, in the present study the cytochemical demonstration of the perinatal change of Ca2+-ATPase activity strongly suggests that the association of this activity with the pancreatic exocrine secretory function. By many morphological and biochemical studies (5,9,11,16,25,26,30,33,39,40), it has been shown that secretory function in rat pancreas starts just after birth and increasingly develops till weaning period (ca. 20 days old).…”
Section: Discussionmentioning
confidence: 99%
“…The developmental change of rat pancreatic exocrine cells has been extensively studied by both biochemical (11,25,27,30,34) and morphological approaches (5,21,25,26,33,39). Term fetal rats (22 day gestation) have fully developed morphological feature of pancreatic exocrine cells (5,21,25,26,33,39), and intracellular synthesis of secretory enzymes such as amylase, chymotrypsinogen, trypsinogen and lipase is almost at adult level (11,25,27,30,34).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Doubling times of 4.7 to 4.9 days for each cell type were similar to estimates derived from labelling indices and confirmed that acinar cell increase did not occur at the expense of ductal elements. In a study of the development of the rat pancreas and parotid from 17 days in titer0 to 40 days post partum Ferraz de Carvalho et al (1978) showed that cytoplasmic volume in the pancreatic acinar cell trebled in this period. From birth the cells mainly got larger without major changes in the volume proportions of the organelles, except for secretion granules which increased.…”
Section: E V E L O P M E N T O F Secretory Cellsmentioning
confidence: 99%